Animate or Inanimate: How Does Animacy Affect Relative Clauses Production for Indonesian and Foreign Learners - Arti Prihatini; Fida Pangesti; Petrus Ari Santoso; Ho Ngoc Hieu (OKARA: Jurnal Bahasa dan Sastra, 2023)
In second language learning, relative clauses are widely studied. However, research comparing Indonesian and foreign learners’ clauses based on animacy has not been widely done. Besides, animacy affects the difficulty of producing relative clauses. Therefore, this study investigates the role of animacy in the production of relative clauses, the relationship between movement distance and the production of relative clauses, and the role of animacy in conformity with the rules of relative clauses. This research employs a descriptive case study. Data was collected from documents on popular article texts of Indonesian and foreign learners of the University of Muhammadiyah Malang. The data were analyzed based on the generative transformation theory developed by Noam Chomsky. The study results show that animacy plays a significant role in producing relative clauses. Indonesian and foreign learners compose more relative clauses on inanimate nouns, which function as subjects, objects, and complements. Foreign learners create more relative objects than subjects. Based on distance, short-movement relative clauses are very productive for Indonesian and foreign learners. Most Indonesian (97%) and foreign (85%) learners have produced relative clauses that conform to the rules. However, relative clauses with inanimate head nouns often break the rules.